2007
DOI: 10.1364/ao.46.008428
|View full text |Cite
|
Sign up to set email alerts
|

Dual-photoelastic-modulator-based polarimetric imaging concept for aerosol remote sensing

Abstract: A dual-photoelastic-modulator- (PEM-) based spectropolarimetric camera concept is presented as an approach for global aerosol monitoring from space. The most challenging performance objective is to measure degree of linear polarization (DOLP) with an uncertainty of less than 0.5% in multiple spectral bands, at moderately high spatial resolution, over a wide field of view, and for the duration of a multiyear mission. To achieve this, the tandem PEMs are operated as an electro-optic circular retardance modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…The MSPI camera design uses a time-varying retardance in the optical path to modulate the orientation of the linearly polarized component of the incoming light, described by the Stokes components Q (excess of horizontally over vertically polarized light) and U (excess of 45° over 135° polarized light) [23][24][25]. Circular polarization V is typically negligible for natural scenes [26,27].…”
Section: Measurement Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The MSPI camera design uses a time-varying retardance in the optical path to modulate the orientation of the linearly polarized component of the incoming light, described by the Stokes components Q (excess of horizontally over vertically polarized light) and U (excess of 45° over 135° polarized light) [23][24][25]. Circular polarization V is typically negligible for natural scenes [26,27].…”
Section: Measurement Techniquementioning
confidence: 99%
“…Electronic circuits were designed and built to meet dual-PEM polarimeter signal timing and phasing requirements in accordance with specifications outlined in [23]. That paper demonstrated that polarimetric accuracy is maximized by properly sampling the video signal and by synchronizing the sampling with the retardance modulation of the dual PEM.…”
Section: Electronicsmentioning
confidence: 99%
“…A conceptual layout of the MSPI instrument. A set of fixed cameras view different angles and a gimbaled camera provides high angular resolution for selected Earth targets and camera-to-camera calibration (Diner et al, 2007).…”
Section: The Multi-angle Spectro-polarimetric Imager (Mspi)mentioning
confidence: 99%
“…This scheme involves two photoelastic modulators that are beating in a carefully selected pattern against each other (Diner et al, 2007). In order to properly sample this modulation pattern, each of the proposed nine cameras in the system needs to read out its imager array about 1000 times per second, resulting in two orders of magnitude more data than can typically be downlinked from the satellite.…”
Section: The Multi-angle Spectro-polarimetric Imager (Mspi)mentioning
confidence: 99%
“…However, the limited information content of such measurements translates into uniqueness problems during the retrieval process, with the result that operational snow products are still limited to snow covered area and albedo (with the exception of the recent addition to MODIS of the dust radiative forcing product as described in Painter et al, 2012). Polarimetric remote sensing (Diner et al, 2007;Cairns et al, 2009;Dubovik et al, 2011;Hasekamp et al, 2011;Chowdhary et al, 2012;Ottaviani et al, 2012a;Knobelspiesse et al, 2012) adds to MODIS-type observations because it can provide information on the ice grain shape Ottaviani et al, 2012b) and an accurate characterization of the optical and microphysical properties of aerosols present in the scene, including possible impurities embedded in the snowpack. The benefits of passive polarimetric observations originate from both their extreme sensitivity to particle microphysics and the specifics of surface polarized reflectance.…”
Section: Introductionmentioning
confidence: 99%